Catabolism of heme in vivo: comparison of the simultaneous production of bilirubin and carbon monoxide - Landaw, Stephen A. (1970)
The quantitative relationship between the catabolism of heme and the formation of bilirubin and carbon monoxide (CO) was studied in untreated rats and in animals treated with phenobarbital or the porphyrogenic drug, allylisopropylacetamide (AIA). A novel metabolic chamber permitting continuous collection of the bile and breath was utilized for quantitation of bilirubin-(14)C and (14)CO after the administration of hematin-(14)C or glycine-(14)C. After intravenous infusion of hematin-(14)C, control and phenobarbital-treated rats produced equimolar amounts of labeled bilirubin and CO; a minor fraction of the infused radioactivity appeared in the bile in other metabolites. The equimolar relationship in the formation of bilirubin and CO was also observed after pulse-labeling with glycine-2-(14)C; in phenobarbital-treated rats both metabolites were formed at an increased rate as compared to controls. By contrast, AIA treatment reduced the fractional conversion of hematin-(14)C to bilirubin and CO; a major fraction of the infused radioactivity appeared in the bile in metabolites other than bilirubin. In addition, in AIA-treated animals the molar CO/bilirubin recovery ratio was consistently greater than 1.0. Comparable results were obtained in AIA-treated rats after pulse-labeling with glycine-2-(14)C. These findings suggest that (a) in control and phenobarbital-treated rats infused hematin and heme formed in the liver are converted predominantly to bilirubin and CO, appearing in equimolar amounts; only a minor fraction of the hematin is degraded to other metabolites; (b) treatment with phenobarbital results in a proportional increase in the formation of both bilirubin and CO, reflecting increased heme synthesis and degradation in the liver; and (c) treatment with the porphyrogenic drug AIA shifts the CO/bilirubin ratio in favor of the gas, and enhances the formation of nonbilirubin metabolites.